2020
DOI: 10.5565/rev/educar.1065
|View full text |Cite
|
Sign up to set email alerts
|

Interest in STEM disciplines and teaching methodologies. Perception of secondary school students and preservice teachers

Abstract: The paper addresses the lack of interest that Secondary Education students display towards the academic disciplines of Science, Technology, Engineering and Mathematics (STEM). From the pedagogical standpoint, the origin of this problem may lie largely in the way these subjects have predominantly been taught, i.e. using expository strategies. The aim of this paper is twofold: first, to examine the retrospective perception that preservice teachers recall about the methodologies used for teaching STEM disciplines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
3
0
4
Order By: Relevance
“…Despite this socio-economic relevance, several studies found a worrying drop in the vocational interest of secondary school students in STEM subjects [6]. A number of aspects have been identified as contributing to this decline in interest.…”
Section: Stem Learning In Secondary Schoolmentioning
confidence: 99%
“…Despite this socio-economic relevance, several studies found a worrying drop in the vocational interest of secondary school students in STEM subjects [6]. A number of aspects have been identified as contributing to this decline in interest.…”
Section: Stem Learning In Secondary Schoolmentioning
confidence: 99%
“…COMDID errubrika kontuan hartuta, bi galdetegi diseinatu dira, COMDID C eta COMDID A. COM-DID C IKDren ezagutza ebaluatzen duen 88 galderatako galdetegia da, ebaluazio objetiboa izanik (Lázaro Cantabrana et al, 2019). COMDID A, berriz, IKDaren autopertzeptzioa hautematen duen 22 galderatako galdetegia da, irakasleak egoera jakin batzuei aurre egiteko duen gaitasunaren pertzeptzioan oinarrituz (Usart Rodríguez et al, 2020). IKDren ezagutza mailaren ebaluazio objetiboa izatea garrantzitsua izatez gain, irakasleek horrekiko duten pertzeptzioa ezagutzea ere oso interesgarria da, irakasleei beren ikaskuntzaren gainean kontzientzia hartzen laguntzen baitie (Usart Rodríguez et al, 2020).…”
Section: Arloko Egoera Eta Ikerketaren Helburuak (Azpiatalak Eta Zerr...unclassified
“…Hezkuntza-eredu honek ikaskuntzaren emaitzetan eta ikasleen trebetasunetan eragin positiboa badu ere (Batdi et al, 2019), ikasleek STEM diziplina, ikasketa eta lanpostuekiko erakusten duten interesa baxua da (European Schoolnet, 2018;Hernández-Serrano eta Muñoz-Rodríguez, 2020).…”
Section: Derrigorrezko Bigarren Hezkuntza Etapako Irakasleen Pertzepzioaunclassified
See 1 more Smart Citation
“…Para la clasificación metodológica existen diversas taxonomías, donde se integran métodos en función de diversos criterios de agrupación, como: el mayor o menor protagonismo del alumnado en los procesos de aprendizaje (Rodríguez-García & Arias-Gago, 2020;Safapour et al, 2019), la etapa educativa a la que se dirigen (Ivanova & Ilyashenko, 2020;Jiménez-Hernández et al, 2020;Mekonnen, 2020;Navaridas, 2004;Njura et al, 2020;Yao & Collins, 2019), el ámbito o disciplina académica que abordan (Hernández-Serrano & Muñoz-Rodríguez, 2020;Mushtaq et al, 2019;Parsak & Saraç, 2020;Sugano & Nabua, 2020) y la ordenación arbitraría de una serie de métodos para utilizarlos como variable dependiente en estudios de tipología empírica (Murphy et al, 2020;Vilaça, 2019;Weir et al, 2019;Zendler, 2019).…”
Section: Introductionunclassified